Marketing terytorialny w działalności samorządu regionalnego - Karpińska, Małgorzata; Rudolf, Wawrzyniec (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Marketing as a consumer orientation philosophy, originally developed for an enterprise, is easily adapted for non profit organizations. Self governments are more and more using the marketing instruments for realizing their tasks. The authors of that article are trying to adapt the marketing concept to the region management realities. They concentrate on so called inward marketing. The authors have critically analysed the implementation of the marketing philosophy in the Marshal's Office operations and have listed the factors constituting the barriers for its implementations. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 690-698